Cultivation Mechanism of Green Technology Innovation in Manufacturing Enterprises Under Environmental Regulations in China - Zhang, Tong-Jian; Zhou, Jian-Ya; Wang, Min; Ren, Kai; Imran, Muhammad; Wang, Rongyu (Frontiers in Environmental Science, 2022)
The rapid development of China's economy is increasing the pressure on the country’s ecological environment. As the largest developing country in the world, China’s environmental crisis is bound to cause global ecological risks. Therefore, green technology innovation is imperative for sustainable development as manufacturing enterprises are heavily affected by the Chinese environment. Through green technology, innovation to help China get rid of the environmental crisis, and then achieve new breakthroughs in the global economy. The Porter hypothesis notes that environmental regulation can promote the growth of green technology innovation capabilities, although the effects have not entirely been felt by China's manufacturing enterprises. This study is based on the structural equation model and considers a sample of China's manufacturing enterprises to empirically test the promotion mechanism of environmental regulation underlying green technology innovation capability. Command-based environmental regulation has the strongest effect on promoting green technology innovation capability, followed by incentive-based environmental regulation. Voluntary environmental regulation has the weakest effect. Green product innovation capability has been well cultivated in the field of green technology innovation capability, followed by green process innovation capability. Terminal technology governance capability is the least developed.